Murder backstage : a novel [large type] - Fletcher, Jessica; Moran, Terrie Farley (Thorndike Press Large Print Mystery, 2024)
"Jessica Fletcher's British cousin, Emma MacGill, will be traveling to Edmonton in Alberta, Canada, to perform with internationally famous star of stage, screen, and television Derek Braverman in an old-fashioned musical review. Emma would love for Jessica to join her there and suggests she bring along some friends. Having just finished her latest book, Jessica is ready for a vacation and is delighted to agree. Dr. Seth Hazlitt and Sheriff Mort Metzger are huge fans of Braverman, so they are eager to tag along, and their fanboy behaviour gives Jessica and Mort's wife, Maureen, more than occasional cause to roll their eyes. Upon arrival in Edmonton, Jessica is quickly outed as mystery writer J. B. Fletcher, and despite numerous protests, a hotel staffer arranges a book signing for her. This and touristy adventures arranged for the group make for a much busier trip than Jessica was expecting. When a hotel bartender, who also happens to be a stagehand for Emma's play, turns up dead backst"--